6. PROPOSED DESIGN OF AN ACTIVE FIRE PROTECTION SYSTEM BASED ON K3 USING ALARM DETECTORS AND SPRINKLERS IN THE WORKING AREA OF AIR SQUADRON 17, HALIM PERDANAKUSUMA AIR BASE - Waspada Tedja Bhirawa; Irwana Syariadi; Basuki Arianto; Suroso; Nur Priyanto; Dwikatama (Jurnal TNI Angkatan Udara, 2026)
This research aims to develop a design proposal for an alarm detector andsprinkler system in the workspace of Air Squadron 17 at Halim Perdanakusuma Air ForceBase. Aircraft hangars are work facilities with a high fire risk due to aircraft maintenanceactivities, the use of technical equipment, the storage of chemicals, and the presence offlammable materials. From an Industrial Engineering perspective, these conditions require thedesign of a safe, reliable, and sustainable work system through the application ofOccupational Safety and Health (OHS) principles. One effective fire risk control measure isthe implementation of an active fire protection system in the form of automatic alarm detectorsand sprinklers. The research methods used included identifying potential fire hazards,analyzing fire protection system requirements, calculating the number and placement of alarmdetectors and sprinklers based on applicable standards, as well as designing pipelines andsummarizing material requirements. References used in the design included the NFPA 13standard and national regulations related to OHS and fire protection. The results of the studyindicate that the proposed alarm detector and sprinkler system design is capable of providingoptimal fire protection throughout the hangar workspace. This design is expected to improvepersonnel safety, protect strategic assets, and support the operational continuity of AirSquadron 17. Furthermore, the results of this study can serve as a technical reference indesigning fire protection systems in similar work facilities.